International Capital Markets : Developments and Prospects, 1983 - Lipsky, John (Occasional Papers; Occasional Paper ;, 1983)
This paper provides a description and analysis of recent developments in international capital (banking and bond) markets and an assessment of market conditions and prospects for financing flows, in particular.